Reliability and validity of the Chinese version of Oldenburg Burnout Inventory for Chinese nurses - Huiwen Xu; Yuan Yuan; Weijuan Gong; Jingyi Zhang; Xinyi Liu; Pingting Zhu; En Takashi; Akio Kitayama; Xiaojuan Wan; Jianhui Jiao (Wiley, 2022)
Abstract Aim This study aims to develop a reliable and validate Chinese version of Oldenburg Burnout Inventory (OLBI). Design A cross‐sectional validation design was adopted in this study. Methods After obtaining the copyright by contacting with the author, the original English OLBI was developed to Chinese by forward translation, back‐translation, cultural adaptation and a pre‐test (20 nurses). The Chinese OLBI and Maslach Burnout Inventory (MBI) were administered to 641 clinical nurses during July and August, 2020. Internal consistency (Cronbach's α coefficient), split reliability (split half coefficient), construct validity (confirmatory factor analysis) and criterion validity (comparison with MBI, using Pearson correlation analysis) were assessed. Results The Chinese OLBI included 16 items. Exploratory factor analysis extracted two factors with a cumulative contribution of 62.245%. Two‐dimensional structure (exhaustion and disengagement) was confirmed. It has good internal consistency (Cronbach's α coefficient values of 0.905, 0.933 and 0.876 for the total questionnaire, exhaustion dimension and disengagement dimension, respectively), split half reliability (split half coefficient = 0.883, p < .01) and criterion validity (r = 0.873, p < .01). Pearson coefficients between 16 items and the scale varied from 0.479-0.765. An acceptable model fit (χ2/df = 2.49, RMSEA = 0.068, TLI = 0.906, CFI = 0.922, SRMR = 0.061) was achieved.